2016
DOI: 10.1016/j.aorn.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Simulations Into Perioperative Education for Undergraduate Nursing Students

Abstract: Incorporating high-fidelity simulations into an undergraduate nursing program's perioperative elective course capitalizes on students' active learning. Simulations allow students the opportunity to assess and participate in clinical scenarios, apply standards, and demonstrate correct nursing actions without compromising patient safety. Incorporating a high-risk, low-volume malignant hyperthermia simulation experience into the undergraduate nursing curriculum emphasizes active learning and provides an opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
7
0
7
Order By: Relevance
“…Some nursing program administrators and faculty members include perioperative concepts in required nursing theory courses and use a simulation laboratory for hands-on experiences. 75,76 One report detailed how a nursing faculty member used a mock OR with a high-fidelity simulator to introduce the concepts of nursing care for the perioperative patient during a malignant hyperthermia crisis and the Quality and Safety Education for Nursing competencies for patient safety and teamwork. 41,75 Some nursing program administrators and faculty members include perioperative concepts in required nursing theory courses and use a simulation laboratory for hands-on experiences.…”
Section: Perioperative Content Integrated Into Required Nursing Theormentioning
confidence: 99%
“…Some nursing program administrators and faculty members include perioperative concepts in required nursing theory courses and use a simulation laboratory for hands-on experiences. 75,76 One report detailed how a nursing faculty member used a mock OR with a high-fidelity simulator to introduce the concepts of nursing care for the perioperative patient during a malignant hyperthermia crisis and the Quality and Safety Education for Nursing competencies for patient safety and teamwork. 41,75 Some nursing program administrators and faculty members include perioperative concepts in required nursing theory courses and use a simulation laboratory for hands-on experiences.…”
Section: Perioperative Content Integrated Into Required Nursing Theormentioning
confidence: 99%
“…It is therefore a possibility to improve skills without putting patients at risk, which implies that simulation is a way of working towards safe care (Brier et al, 2015;Mullen & Byrd, 2013). Bashaw's (2016), study investigating the integration of simulation into nursing education, showed that students increased their confidence with simulation indicating that simulation is beneficial to the students'…”
Section: Simulationmentioning
confidence: 99%
“…Curricula containing debriefing after critical events have been noted in the nursing literature, and programs/studies exist for multidisciplinary teams in both the operating room and other settings. 20,43,44 While debriefing with more team members may hypothetically have more barriers, there is evidence from real-time use that it can also improve efficiency and patient outcomes. 45,46 The pendulum of a critical event's impact swings on a continuum, where on one end is provider burnout, compromised patient safety, and adverse events, and on the other end is provider resilience and the ability for providers to serve as a buffer to protect patients from an imperfect system.…”
Section: Discussionmentioning
confidence: 99%